PENGENALAN DAN PENERAPAN LAPORAN KEUANGAN BERBASIS MICROSOFT EXCEL PADA KOPERASI DI DESA PATONGKO KABUPATEN SINJAI - Andi Urfia Awaliah,; Mahyudin Usman, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Patongko Village in Sinjai Regency is one of the areas involved in the Koperasi Merah Putih program, a government initiative aimed at strengthening rural economies through cooperative development. However, field realities show that cooperative management still faces several challenges, such as low financial literacy, limited use of information technology, and minimal understanding among cooperative leaders about financial reports. The Community Service Program (PKM) conducted in June 2025 aimed to introduce and train the use of Microsoft Excel as a tool in preparing cooperative financial reports. The method used was a qualitative literature study combined with participatory observation during training sessions involving 22 cooperative participants. The results showed that practical and participatory approaches were effective in improving participants’ understanding of digital financial recording, although challenges in infrastructure and technological literacy remained. This study emphasizes the importance of strengthening the human resource capacity of cooperatives through contextual training based on simple technology as an initial step toward the digitalization of financial management in rural cooperatives